2001
DOI: 10.1626/pps.4.136
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Assimilates to Each Organ in Rice Plants Exposed to a Low Temperature at the Ripening Stage, and the Effect of Brassinolide on the Distribution

Abstract: : Previously, we found that promotion of ripening by brassinolide (BR) in rice plants is attributable to the rapid translocation of assimilates from leaves to the panicle (Fujii and Saka, 1992). In this study, we examined the effect of BR treatment on the distribution aspects of carbohydrates (starch, sucrose, glucose and fructose) in upper organs including the panicle of the rice plant (cv. Nipponbare) grown in a low temperature condition(20,C in the daytime / 13,C at night) in a phytotron under natural dayli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 9 publications
0
18
0
2
Order By: Relevance
“…Grain yield of a cereal crop depends on both number and size of grains (Grieve et al 1992), but from the results for different yield components as observed in the present study, it is clear that exogenously applied 24-epiBL did not improve the grain yield or yield components of hexaploid wheat. In the present study, 24-epiBL was applied to 41-days old plants, but it has been reported that the BR is effective for improving grain yield when it is applied at the heading stage, as has been found earlier in rice (Fujii and Saka 2001).…”
Section: Discussionmentioning
confidence: 55%
“…Grain yield of a cereal crop depends on both number and size of grains (Grieve et al 1992), but from the results for different yield components as observed in the present study, it is clear that exogenously applied 24-epiBL did not improve the grain yield or yield components of hexaploid wheat. In the present study, 24-epiBL was applied to 41-days old plants, but it has been reported that the BR is effective for improving grain yield when it is applied at the heading stage, as has been found earlier in rice (Fujii and Saka 2001).…”
Section: Discussionmentioning
confidence: 55%
“…Experiments involving exogenous BR application on wheat and soybean (Glycine max) plants and seeds suggest that BRs might significantly affect it (Janeczko et al, 2009(Janeczko et al, , 2010. In rice, treatment with BRs at anthesis increased starch content in kernels (Fujii and Saka, 2001). Additional studies on the BR effects on seed composition are needed if the BR pathway components are to be manipulated for grain crop improvement.…”
Section: Seed Development and Seed Fillingmentioning
confidence: 99%
“…(Ali et al , 2008aArora et al 2008;Hayat et al 2007;Janeczko et al 2009;Kartal et al 2009;Mazorra et al 2002;Ö zdemir et al 2004;Shahbaz et al 2008;Singh and Shono 2005). Photosynthesis, transpiration and nitrogen fixation in plants are also influenced by BRs (Ali et al 2008b;Fariduddin et al 2003;Farooq et al 2009;Hayat et al 2000;Li et al 2008;Sairam 1994a, b;Swamy and Rao 2008;Yu et al 2004), as well as the distribution of assimilates to various plant organs (Fujii and Saka 2001).…”
Section: Introductionmentioning
confidence: 99%